HUMAN HEALTH EFFECTS OF AIR CONDITIONERS - Ozcimen, Didem; Terzioglu, Pinar; Yucel, Sevil (YILDIZ TECHNICAL UNIV, 2012)
Air conditioners which are used in buildings can be useful or harmful for human health. A wrong place or poor quality of air conditioners is harmful factors for health. Many bacteria and fungi can be also proliferated because of dense and water accumulations in cooling systems. These problems can cause illness and some symptoms called sick building syndrome. Generally building occupants who have this syndrome complain of symptoms such as sensory irritation of the eyes, nose, and throat; neurotoxic or general health problems; skin irritation; odor and taste sensations. On the other hand, scientific authorities proved that air-conditioners can have great benefits for human health when they are used consciously. Especially the usage of air conditioners is recommended to the people that are old and diabetic, and heart patients. Moreover, air conditioners which are used in buildings have the important negative effects on environment such as the effects of cooling fluids on ozone layer and global warming, and energy consumption. In this study, the effects of air conditioners used in the buildings on the human health were evaluated by comparison of the pros and cons.
Keywords: Air conditioners; air conditioning filters; sick building syndrome; human health; Engineering